Perubahan Sumber Daya Insani Pendidikan Uin Sulthan Thaha Saifuddin Jambi di Era Disrupsi dan Covid-19 - As'ad, As'ad (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
The Covid-19 pandemic has accelerated the digital transformation of Indonesian education. A case study research with a qualitative approach is designed to describe the transformation of educational human resources at UIN Sulthan Thaha Saifuddin Jambi. Data was collected by interviewing the leadership of UIN Sulthan Thaha Saifuddin Jambi, observation, and documentation. The first study's findings show that the era of disruption and the Covid-19 pandemic have encouraged UIN Sulthan Thaha Saifuddin Jambi to transform human resources. Second, UIN Sulthan Thaha Saifuddin Jambi's human resources must start to apply the corporate mindset. Third, the Covid-19 pandemic has forced the management of UIN Sulthan Thaha Saifuddin Jambi to adapt to changes in work culture. Fourth, in Islam, the spirit of change is Islamic teaching, as stated in Surah Ar-Ra'd:11.